THE EFFECT OF TEACHING READINESS ON TEACHER PERFORMANCE IN THE NEW NORMAL ERA (CASE STUDY: MTs SWASTA YAPI AEK SONGSONGAN) - Rismayani Rismayani; Eliana Ayu Lestari; Fitri Lestari; Mavianti Mavianti (Proceeding International Seminar of Islamic Studies, 2021)
This study discusses the effect of teaching readiness on teacher performance in the new normal era. This study aims to identify and obtain information about how important the readiness of teachers is in preparing for the new normal era of learning. How is the effect of teaching readiness on the learning process in the new normal period? This study used a combination of qualitative case study methods by conducting interviews with 5 respondents at the MTsS YAPI Aek Songsongan area to obtain information about the teacher's teaching readiness in preparing for learning in the new normal era and to complete and deepen the information related to this research obtained by using the method. quantitative, namely taking some information through literature study reference sources. With the aim of maintaining confidentiality, respondents were given the initials A1, A2, A3, A4, and A5. The technique used in this data collection is a questionnaire in the form of a questionnaire, in which the questionnaires distributed are closed so that respondents simply choose the answers provided, then conduct interviews with respondents. From the observations in the new normal era, it can be seen that the teaching readiness of teachers is very influential on the performance of teachers in preparing for learning in the new normal era so that learning planning can be said to be good. Based on observations of teacher work performance at MTsS YAPI Region Aek Songsongan in the new normal era, it looks still low.Keywords: Teaching Readiness, Performance, New Normal.